Implementation of Stunting Reduction Acceleration Program at Kapan Public Health Center, Mollo Utara District, South Central Timor Regency - Fanderio Rafael BANUNAEK; David B. W. PANDIE; Hendrik TODA (International Journal of Environmental, Sustainability, and Social Science, 2024)
Stunting is a chronic nutritional problem that affects children's growth and development. This study aims to analyze the implementation of the stunting reduction acceleration program at Kapan Public Health Center. The method used is descriptive qualitative with data collection through interviews, observations, and documentation. The results of the study showed that although there was a decrease in stunting cases from 726 to 556 cases in 2023, the stunting rate increased again to 777 cases in 2024. Inhibiting factors include lack of public knowledge, limited supervision, and suboptimal policy planning. In seeing the success of policy implementation, policy implementation can be studied based on Merilee S. Grindle's theory by referring to 2 major variables, namely policy content and policy context. This study also looks at the success of the implementation of Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction in the working area of the Kapan Health Center, North Mollo District, South Central Timor Regency. This study recommends increasing cross-sector collaboration and community education to prevent stunting.